Analysis of Population Control Policy and Implementation of Family Planning Villages in Improving Socio-Economic Development in Indonesia: Literature Review - Suardi Mukhlis; Muhammad Suyuti; Abdul Ganie Gaffar; Jusniati Jusniati (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Population issues present a significant challenge for Indonesia, impacting social, economic, and environmental well-being. High population growth, uneven distribution, and the need for improved human resource quality are critical concerns demanding attention. This literature review analyzes population control policies implemented by the Indonesian government, particularly those initiated by the National Population and Family Planning Agency (BKKBN). Focusing on the Family Planning Village (KB Village) program, this study examines its approach to improving community quality of life through family planning, education, health, and economic empowerment. The review reveals that effective population control extends beyond birth rate reduction to encompass efforts that balance population growth with socio-economic development. The success of such programs is influenced by factors including effective communication, resource availability, implementer disposition, and a supportive bureaucratic structure. Therefore, this review argues that strengthening the capacity of regional bureaucracies, especially in high-growth areas, is crucial for achieving sustainable population control.